Sex work and the state : during nation-building years 1959 -1999 - Kiam, Jesslyn Jian Hui (2019)
This study attempts to explicate the politics of sex work spaces and health hygiene during the nation-building period in Singapore (1959 to 1990s) in which the state accentuated industrialisation. Through two case studies of sex work spaces and an investigation of the public’s sex health, this study will argue that Singapore had constructed a productive state identity imperative for its nation-building period in 1959 to 1990s. Firstly, urban redevelopments carried out by the state had segregated “licensed” sex work areas to a moral geography, so as to underline heteronormativity as indispensable to a productive state identity, yet, illuminated the inequalities in the practice of sex work and sex workers. Secondly, the state reconfigured medical spaces to assemble and strengthen their medical knowledge on Sexually Transmitted Diseases, and to use the knowledge as an apparatus of power to discipline and regulate the health of the sex workers and the public. It aimed to ensure a safe and healthy present and future working population that was essential for a productive state identity.